Habilitation of Patients with Congenital Malformations Associated with Thalidomide: Prosthetic Aspects - Gilpin, R. E. (1963)
The types of prostheses available for treatment of congenital amputations in children, and the assistance in habilitation which can be expected from their use, are described in this communication. The limb deformities in children commonly associated with the drug thalidomide are phocomelia and amelia. Prosthetic treatment of these is difficult, but in almost every case some assistance can be offered. The degree of this assistance will depend to a large extent on (1) the number of limbs involved, (2) the site of the deformity, (3) the intellectual capacity of the child. These factors are evaluated by a clinic team, consisting of a prosthetist, a therapist, a social worker, and a doctor, who acts as the clinical chief. They are also embodied into a prescription for a prosthesis and into a program of management. Subsequently, the clinic team also carry out an assessment of the result. The prosthetist makes available his knowledge of present-day appliances, and assures that the way is left open for use of new, and perhaps revolutionary prostheses, in the future.